Concrete early strength agent as well as preparation method and application thereof

By using nano-silicon calcium components and specific modified components in concrete, a concrete early strength agent with good early strength effect under low temperature conditions was prepared, which solved the problem of limited early strength effect and damaged later mechanical properties in the prior art, and achieved efficient early strength performance improvement and later performance protection.

CN119528480APending Publication Date: 2025-02-28KZJ NEW MATERIALS GROUP CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411649467.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The existing concrete early strength agent has limited early strength effect under low temperature conditions and has an adverse effect on the later mechanical properties of concrete.

Method used

Components such as nano-calcium silicone components, silicate compounds, organosiloxane compounds, hydrophobic surfactants and polymers with long side chain steric hindrance effects were prepared by hydrolysis and condensation reaction and ultrasonic treatment.

Benefits of technology

It significantly improves the early strength performance of concrete under low temperature conditions, while maintaining the stability of later mechanical properties, avoiding the adverse effects of traditional early strength agents on concrete properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005140518020000101
    Figure BDA0005140518020000101
  • Figure BDA0005140518020000111
    Figure BDA0005140518020000111
Patent Text Reader

Abstract

The invention belongs to the technical field of concrete early strength agents, and relates to a concrete early strength agent special for low-temperature and negative-temperature conditions and a preparation method and application thereof. The concrete early strength agent provided by the invention contains a nano silicon-calcium component, a first modified component, a second modified component, a third modified component, a fourth modified component, an optional neutralizer and water, and the nano silicon-calcium component simultaneously contains a nano silicon component and a nano calcium component. The first modified component is obtained by carrying out hydrolytic condensation reaction on a silicate ester compound, an organosiloxane compound and an inorganic silicon compound and / or nanocrystalline cellulose, the second modified component simultaneously contains polyol and carboxylate and / or nitrate, and the third modified component is a hydrophobic surfactant. The fourth modified component is a polymer with a long side chain steric hindrance effect. The concrete early strength agent has a good early strength effect and does not influence the later mechanical properties of concrete.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of concrete early strength agents, and in particular relates to a special concrete early strength agent for low-temperature and negative-temperature conditions, and a preparation method and application thereof. Background Art

[0002] As the most important material in civil engineering construction, concrete plays an extremely important role. However, due to the limitations of concrete's own composition materials, it cannot fully meet the needs of various projects. In northern my country, the winter temperature is generally below 5°C, and the extreme minimum temperature is even close to -40°C. For some projects constructed in cold seasons, in order to avoid early freezing damage to concrete, ensure that concrete can continue to undergo hydration reactions at low temperatures, and reduce the cost of winter construction, concrete needs to have characteristics such as early strength and frost resistance.

[0003] Early strength agent is a concrete admixture developed to solve the problem that emergency projects cannot be constructed normally due to restrictions on site, construction period, time or progress. It has multiple functional characteristics such as fast setting and early strength, good durability and high safety. Traditional early strength admixtures include inorganic salts (chlorides, sulfates, phosphates, sulfates), organic amines, inorganic salt activators and ultrafine powders. However, these traditional early strength admixtures have limited improvement on the early strength effect of concrete, and will also have a great impact on the later mechanical properties and durability of concrete. In view of this, it is urgent to develop a concrete early strength agent that can effectively improve the early strength performance of concrete under low temperature and negative temperature conditions without loss of later mechanical strength. Summary of the invention

[0004] The first purpose of the present invention is to overcome the defects of existing concrete early strength agents that have limited early strength effect and will affect the later mechanical properties of concrete, and to provide a new concrete early strength agent that has good early strength effect and will not affect the later mechanical properties of concrete.

[0005] The second object of the present invention is to provide a method for preparing the above-mentioned concrete early strength agent.

[0006] The third object of the present invention is to provide application of the above concrete early strength agent in low-temperature concrete.

[0007] Specifically, the concrete early strength agent provided by the present invention contains a nano-calcium silicon component, a first modifying component, a second modifying component, a third modifying component and a fourth modifying component, as well as an optional neutralizing agent and water, wherein the nano-calcium silicon component contains both a nano-silica component and a nano-calcium component, the first modifying component is obtained by hydrolysis and condensation reaction of a silicate compound, an organic siloxane compound, an inorganic silicon compound and / or nano-microcrystalline cellulose in the presence of a cationic compound and a dispersion stabilizer, the second modifying component contains both a polyol and a carboxylate and / or a (sub)nitrate, the third modifying component is a hydrophobic surfactant, and the fourth modifying component is a polymer having a long side chain steric hindrance effect.

[0008] The preparation method of the concrete early strength agent provided by the invention comprises uniformly mixing a nano-silicon calcium component, a first modified component, a second modified component, a third modified component and a fourth modified component as well as an optional neutralizer and water to obtain the concrete early strength agent.

[0009] The key to the present invention is to cooperate the nano-silicon calcium component and the specific first modifying component, the second modifying component, the third modifying component and the fourth modifying component, so that the obtained concrete early strength agent has good early strength effect and will not affect the later mechanical properties of concrete. The reason may be as follows: on the one hand, the hydration reaction of cement particles will form dicalcium silicate (C2S), tricalcium silicate (C3S), calcium vanadium (Aft) and hydrated calcium silicate gel (CSH). The formation of these substances is the key to improving strength, and the nano-calcium silicate component and the first modified component can perform intercalation composite modification on the hydrated calcium silicate gel, promote cement hydration, provide crystal nucleus inducing components in the early stage of cement hydration, reduce the nucleation barrier of cement hydration products, further accelerate the hydration of mineral components in cement, and improve the early strength performance of concrete; on the other hand, the interaction between the second modified component and the third modified component can not only effectively improve the strength performance of concrete under low temperature and negative temperature conditions, but also keep the concrete in good workability to avoid affecting the later mechanical properties; on the other hand, adding a polymer with a long side chain steric hindrance effect to the concrete early strength agent can effectively maintain the dispersion performance of concrete, so that while ensuring the normal hydration of cement, the dispersion degree of the hydrated calcium silicate crystal nucleus can be further improved, exposing more CSH active sites, and improving the later mechanical properties. DETAILED DESCRIPTION

[0010] The concrete early strength agent provided by the present invention contains a nano-silicon calcium component, a first modifying component, a second modifying component, a third modifying component and a fourth modifying component, and an optional neutralizer and water. The weight ratio of the nano-silicon calcium component, the first modifying component, the second modifying component, the third modifying component, the fourth modifying component and water is 100: (150-300): (90-160): (10-40): (180-320): (2500-3500). Based on 100 parts by weight of the nano-silicon calcium component, the content of the first modified component is preferably 150 to 300 parts by weight, such as 150, 180, 200, 220, 240, 260, 280, 300 parts by weight or any value therebetween; the content of the second modified component is preferably 90 to 160 parts by weight, such as 90, 100, 110, 120, 130, 140, 150, 160 parts by weight or any value therebetween; the content of the third modified component is preferably 10 to 40 parts by weight, such as 10, 15, 20, 25, 30, 35, 40 parts by weight or any value therebetween; the content of the fourth modifying component is 180-320 parts by weight, such as 180, 190, 200, 220, 240, 260, 280, 300, 320 parts by weight or any value therebetween; the content of water is 2500-3500 parts by weight, such as 2500, 2600, 2700, 2800, 2900, 3000, 3100, 3200, 3300, 3400, 3500 parts by weight or any value therebetween. The amount of the neutralizer is based on controlling the pH value of the concrete early strength agent to 6-7, specifically 6, 6.2, 6.4, 6.6, 6.8, 7 or any value therebetween.

[0011] In a preferred embodiment, the content of the nano-silicon calcium component is 13 to 16 parts by weight, the content of the first modified component is 25 to 35 parts by weight, the content of the second modified component is 15 to 20 parts by weight, the content of the third modified component is 2 to 5 parts by weight, the content of the fourth modified component is 30 to 40 parts by weight, and the content of water is 400 to 420 parts by weight. At this time, the components can play a better synergistic compounding role, and the early strength effect and later mechanical properties of the obtained concrete accelerator are better. Specifically, the content of the nano-silicon calcium component can be 13, 14, 15, 16 parts by weight or any value therebetween; the content of the first modified component can be 25, 28, 30, 32, 35 parts by weight or any value therebetween; the content of the second modified component can be 15, 16, 17, 18, 19, 20 parts by weight or any value therebetween; the content of the third modified component can be 2, 3, 4, 5 parts by weight or any value therebetween; the content of the fourth modified component can be 30, 32, 34, 36, 38, 40 parts by weight or any value therebetween; the content of water can be 400, 402, 404, 406, 408, 410, 412, 414, 416, 418, 420 parts by weight or any value therebetween.

[0012] In the present invention, the nano-silicon calcium component contains both a nano-silicon component and a nano-calcium component. The mass ratio of the nano-silicon component to the nano-calcium component is preferably (10-15):(18-23), specifically 10:(18-23) (such as 10:18, 10:20, 10:21, 10:23, etc.), 12:(18-23) (such as 12:18, 12:20, 12:21, 12:23, etc.), 14:(18-23) (such as 14:18, 14:20, 14:21, 14:23, etc.), 15:(18-23) (such as 15:18, 15:20, 15:21, 15:23, etc.) or any value therebetween. The nano silicon component can be at least one of sodium metasilicate pentahydrate, sodium metasilicate nonahydrate, tetraethyl orthosilicate, tetrabutyl orthosilicate, potassium silicate, lithium silicate and sodium orthosilicate. The nano calcium component is preferably a soluble calcium source, specifically at least one of calcium formate, calcium acetate, calcium chloride, calcium gluconate and calcium nitrate tetrahydrate.

[0013] In the present invention, the first modified component is obtained by hydrolysis and condensation reaction of a silicate compound, an organic siloxane compound, an inorganic silicon compound and / or nano-microcrystalline cellulose in the presence of a cationic compound and a dispersion stabilizer. The mass ratio of the silicate compound, the organic siloxane compound, the inorganic silicon compound and / or nano-microcrystalline cellulose, the dispersion stabilizer and the cationic compound is (10-20):(15-18):(25-30):(40-50):(5-8). Specifically, the content of the silicate compound can be 10 to 20 parts by weight, such as 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20 parts by weight or any value therebetween; the content of the organosiloxane compound can be 15 to 18 parts by weight, such as 15, 16, 17, 18 parts by weight or any value therebetween; the content of the inorganic silicon compound and / or nano-microcrystalline cellulose can be 25 to 30 parts by weight, such as 25, 26, 27, 28, 29, 30 parts by weight or any value therebetween; the content of the dispersant can be 40 to 50 parts by weight, such as 40, 42, 44, 46, 48, 50 parts by weight or any value therebetween; the content of the cationic compound can be 5 to 8 parts by weight, such as 5, 6, 7, 8 parts by weight or any value therebetween. It should be noted that when only one of the inorganic silicon compound and nano-microcrystalline cellulose is used in the preparation process of the first modified component, the content of the inorganic silicon compound and / or nano-microcrystalline cellulose refers to the content of the inorganic silicon compound or nano-microcrystalline cellulose; when the inorganic silicon compound and nano-microcrystalline cellulose are used simultaneously in the preparation process of the first modified component, the content of the inorganic silicon compound and / or nano-microcrystalline cellulose refers to the total content of the inorganic silicon compound and nano-microcrystalline cellulose. The silicate compound can be listed as at least one of ethyl orthosilicate, propyl orthosilicate, tetraethyl orthosilicate, tetrabutyl orthosilicate, trimethylsilyl acetate, ethyl trimethylsilyl acetate and trimethylsilyl acetate. The organosiloxane compound can be listed as at least one of vinyl tris(2-methoxyethoxy)silane, γ-aminopropyl triethoxysilane, γ-(2,3-epoxypropyloxy)propyl dimethylethoxysilane, γ-methacryloxypropyl trimethoxysilane and allyl triethoxysilane. The inorganic silicon compound may be at least one of nano silicon dioxide, sodium silicate, potassium silicate and aluminum silicate. The dispersion stabilizer preferably contains a nonionic surfactant and a dispersion solvent at the same time. Among them, the nonionic surfactant may be at least one of polyoxyethylene fatty acid ester, sorbitan fatty acid ester, polyoxyethylene alkyl alcohol ether, polyoxyethylene alkylphenol ether, polyoxyethylene fatty amine, polyoxyethylene alkylamide, sorbitan fatty acid ester polyoxyethylene ether, etc., and polyoxyethylene (5) nonylphenyl ether is particularly preferred. The dispersion solvent may be at least one of n-hexane, cyclohexane, dichloromethane, chloroform, etc., and cyclohexane is particularly preferred.The cationic compound can be at least one of hexadecyl trimethyl ammonium chloride, tetradecyl dimethyl benzyl ammonium chloride, methacryloyloxyethyl trimethyl ammonium chloride, dimethylaminoethyl methacrylate and trimethylammonium ethyl methacrylate. In addition, the conditions of the hydrolysis condensation reaction preferably include a temperature of 40°C to 50°C, such as 40°C, 42°C, 44°C, 46°C, 48°C, 50°C or any value therebetween; and a time of 1h to 5h, such as 1h, 2h, 3h, 4h, 5h or any value therebetween.

[0014] In the present invention, the second modifying component contains polyols and carboxylates and / or (sub)nitrates at the same time. Wherein, the mass ratio of the content of polyols in the second modifying component to the total content of carboxylates and (sub)nitrates is (1-5): (15-25). Specifically, the content of the polyols can be 1, 2, 3, 4, 5 parts by weight or any value therebetween; the total content of the carboxylates and (sub)nitrates is 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25 parts by weight or any value therebetween. The polyols can be listed as at least one of ethylene glycol, diethylene glycol, glycerol and diethylene glycol. The carboxylates can be listed as at least one of calcium formate, potassium formate, sodium formate, calcium acetate, potassium acetate and sodium acetate. The (sub)nitrate includes nitrates, nitrites or a mixture of nitrates and nitrites, and specifically can be listed as at least one of sodium nitrite, potassium nitrite, calcium nitrite, sodium nitrate, potassium nitrate and calcium nitrate.

[0015] In the present invention, the third modifying component is a hydrophobic surfactant, preferably at least one selected from octadecyltrimethylammonium chloride, cocamidopropyl betaine, lauramidopropyl hydroxysulfobetaine, cocamidopropyl hydroxysulfobetaine and sodium α-olefin sulfonate.

[0016] In the present invention, the fourth modified component is a polymer with a long side chain steric hindrance effect, preferably at least one of an acrylic polymer, a methacrylic polymer, a polyamide, a polyimide, a polyethylene and a polyethylene glycol. In addition, the number average molecular weight of the fourth modified component is preferably 3000 to 6000 g / mol, such as 3000, 3200, 3400, 3600, 3800, 4000, 4200, 4400, 4600, 4800, 5000, 5200, 5400, 5600, 5800, 6000 g / mol or any value therebetween.

[0017] In the present invention, the neutralizing agent can be any existing reagent capable of adjusting the pH value of the concrete early strength agent, and can include at least one of sodium methoxide, sodium hydroxide, potassium hydroxide, sodium bicarbonate, potassium bicarbonate, sodium acetate, potassium acetate, dimethylethanolamine and triisopropanolamine.

[0018] The preparation method of the concrete early strength agent provided by the invention comprises uniformly mixing a nano-silicon calcium component, a first modified component, a second modified component, a third modified component and a fourth modified component as well as an optional neutralizer and water to obtain the concrete early strength agent.

[0019] In a preferred embodiment, the mixing method comprises the following steps:

[0020] S1. Dispersing the nano-silicon component and the nano-calcium component in the fourth modified component II to obtain a product containing the nano-silicon-calcium component; dissolving the cationic compound and the dispersion stabilizer in the fourth modified component I to obtain a dispersion, and then dropping a mixture of a silicate compound, an organic siloxane compound, an inorganic silicon compound and / or nano-microcrystalline cellulose into the dispersion at 40°C to 50°C, and keeping the mixture warm after the addition is completed to obtain a product containing the first modified component; uniformly mixing the polyol with the carboxylate and / or (sub)nitrate to obtain a second modified component;

[0021] S3. The product containing nano-silicon calcium component, the third modified component and the fourth modified component are mixed evenly, the resulting composite liquid is mixed evenly with the product containing the first modified component and the second modified component, and then the pH value of the resulting mixed liquid is adjusted to 6 to 7 using a neutralizer to obtain a concrete early strength agent.

[0022] The present invention also provides the use of the concrete early strength agent in low temperature concrete. In addition, the dosage of the concrete early strength agent in concrete is preferably 0.5-0.8% of the mass of the gel material, such as 0.5%, 0.6%, 0.7%, 0.8% or any value therebetween.

[0023] The present invention will be described in detail below through examples.

[0024] In the following examples and comparative examples, the amounts of raw materials used are all by weight.

[0025] Example 1

[0026] This example is used to illustrate the concrete early strength agent provided by the present invention and its preparation method

[0027] S1. Take 100 parts of the fourth modified component (polymethyl acrylate with a number average molecular weight of 3000) as the reaction base material, and at a temperature of 45°C and a stirring speed of 600rpm, add 12 parts of nano-silica component (sodium metasilicate pentahydrate) and 20 parts of nano-calcium component (calcium formate) to the reaction base material at the same time, respectively. The dropping time is controlled at 3.0h. During the dropping process, the pH value is continuously adjusted to 6 with an alkaline solution. After the dropping is completed, the temperature is kept for 2h, and the resulting solution is collected as a product containing nano-silica-calcium components.

[0028] 5 parts of methacryloyloxyethyl trimethylammonium chloride and 45 parts of a dispersion stabilizer (a mixture of polyoxyethylene (5) nonylphenyl ether and cyclohexane solution in a volume ratio of 1:6) are added to 50 parts of the fourth modified component (polymethyl acrylate with a number average molecular weight of 3000). At a temperature of 45°C and a stirring speed of 600 rpm, 15 parts of tetrabutyl orthosilicate, 18 parts of γ-aminopropyl triethoxysilane and 25 parts of nano-microcrystalline cellulose are added dropwise at the same time. The addition time is controlled at 2.0 h. After the addition is completed, the mixture is kept warm for 1 h, and the resulting solution is collected, which is the product containing the first modified component.

[0029] Mix 3 parts of ethylene glycol with 20 parts of sodium nitrite, and stir continuously at 30°C for 1.0 hour. The resulting solution is the antifreeze component.

[0030] S2. Add 15 parts of the product containing nano-silicon calcium component, 3 parts of the third modified component (octadecyl trimethyl ammonium chloride), 30 parts of the fourth modified component (polymethyl acrylate with a number average molecular weight of 3000 g / mol) and 400 parts of water into a reaction vessel, place the reaction vessel in a microwave reactor for ultrasonic treatment for 1.0 h, and obtain a uniformly dispersed composite liquid. Add 30 parts of the product containing the first modified component and 18 parts of the second modified component to the composite liquid, heat it in a 50°C water bath for 1.5 h, add 20 parts of water, then add a neutralizer to adjust the pH value to 6.5, and the resulting solution is a concrete early strength agent.

[0031] Example 2

[0032] This example is used to illustrate the concrete early strength agent provided by the present invention and its preparation method

[0033] S1. Take 100 parts of the fourth modified component (polyamide with a number average molecular weight of 6000) as the reaction base material, and at a temperature of 45°C and a stirring speed of 600rpm, add 10 parts of 10 nanometer silicon component (tetraethyl orthosilicate) and 23 parts of nanometer calcium component (calcium chloride) to the reaction base material respectively, and the dropping time is controlled at 3.0h. During the dropping process, the pH value is continuously adjusted to 7 with an alkaline solution. After the dropping is completed, the temperature is kept for 2h, and the resulting solution is collected as a product containing nano-silicon-calcium components.

[0034] 8 parts of hexadecyltrimethylammonium chloride and 40 parts of a dispersion stabilizer (a mixture of polyoxyethylene (5) nonylphenyl ether and cyclohexane solution in a volume ratio of 1:6) are added to 50 parts of the fourth modified component (polyamide with a number average molecular weight of 6000 g / mol). At a temperature of 40°C and a stirring speed of 600 rpm, 10 parts of trimethylsilyl acetate, 15 parts of vinyl tri(2-methoxyethoxy) silane and 28 parts of nano-silica are added dropwise at the same time. The addition time is controlled at 2.0 h. After the addition is completed, the mixture is kept warm for 5 h, and the resulting solution is collected, which is a product containing the first modified component.

[0035] Mix 1 part of diethylene glycol with 25 parts of sodium nitrite, and stir continuously for 1.0 hour at 30°C. The resulting solution is the antifreeze component.

[0036] S2. Add 15 parts of the product containing nano-silicon calcium component, 5 parts of the third modified component (cocoamidopropyl betaine), 30 parts of the fourth modified component (polyamide with a number average molecular weight of 6000) and 400 parts of water into a reaction vessel, place the reaction vessel in a microwave reactor for ultrasonic treatment for 1.0h, and obtain a uniformly dispersed composite liquid. Add 28 parts of the product containing the first modified component and 15 parts of the second modified component to the composite liquid, heat it in a 50°C water bath for 1.5h, add 20 parts of water, then add a neutralizer to adjust the pH value to 7, and the resulting solution is a concrete early strength agent.

[0037] Example 3

[0038] This example is used to illustrate the concrete early strength agent provided by the present invention and its preparation method

[0039] S1. Take 100 parts of the fourth modified component (polyethylene glycol with a number average molecular weight of 4000) as the reaction base, and add 15 parts of nano-silica component (potassium silicate) and 18 parts of nano-calcium component (calcium gluconate) to the reaction base at the same time at a temperature of 45°C and a stirring speed of 600rpm. The addition time is controlled at 3.0h. During the addition process, the pH value is continuously adjusted to 6.5 with an alkaline solution. After the addition is completed, the temperature is kept for 2h, and the resulting solution is collected as a product containing nano-silica-calcium components.

[0040] 6 parts of dimethylaminoethyl methacrylate and 50 parts of a dispersion stabilizer (a mixture of polyoxyethylene (5) nonylphenyl ether and cyclohexane solution in a volume ratio of 1:6) are added to 50 parts of the fourth modified component (polyethylene glycol with a number average molecular weight of 4000 g / mol). At a temperature of 42°C and a stirring speed of 600 rpm, 20 parts of ethyl trimethylsilyl acetate, 16 parts of γ-methacryloxypropyltrimethoxysilane and 30 parts of sodium silicate are added dropwise at the same time. The addition time is controlled at 2.0 h. After the addition is completed, the mixture is kept warm for 3 h, and the resulting solution is collected, which is the product containing the first modified component.

[0041] Mix 5 parts of propylene glycol with 15 parts of calcium nitrate, and stir continuously at 30°C for 1.0 hour. The resulting solution is the antifreeze component.

[0042] S2. Add 15 parts of the product containing nano-silicon calcium component, 2 parts of the third modified component (laurylamide propyl hydroxysulfobetaine), 30 parts of the fourth modified component (polyethylene glycol with a number average molecular weight of 4000) and 400 parts of water into a reaction vessel, place the reaction vessel in a microwave reactor for ultrasonic treatment for 1.0h, and obtain a uniformly dispersed composite liquid. Add 30 parts of the product containing the first modified component and 18 parts of the second modified component to the composite liquid, heat it in a 50°C water bath for 1.5h, add 20 parts of water, and then add a neutralizer to adjust the pH value to 6.8. The resulting solution is a concrete early strength agent.

[0043] Comparative Example 1

[0044] A concrete early strength agent was prepared according to the method of Example 1, except that the nano-silica component was replaced by the same weight portion of the nano-calcium component. The other conditions were the same as those of Example 1 to obtain a concrete early strength agent.

[0045] Comparative Example 2

[0046] A concrete early strength agent was prepared according to the method of Example 1, except that the second modified component was replaced by the third modified component in the same weight portion, and the other conditions were the same as those of Example 1 to obtain a concrete early strength agent.

[0047] Comparative Example 3

[0048] A concrete early strength agent was prepared according to the method of Example 1, except that the third modified component was replaced by the second modified component in the same weight portion, and the other conditions were the same as those of Example 1 to obtain a concrete early strength agent.

[0049] Comparative Example 4

[0050] A concrete early strength agent was prepared according to the method of Example 1, except that the ethylene glycol in the second modified component was replaced by the same weight portion of sodium nitrite, and the other conditions were the same as in Example 1 to obtain a concrete early strength agent.

[0051] Test Case

[0052] The early strength effect and later mechanical properties of the concrete early strength agent obtained in the above embodiments and comparative examples were tested according to the following methods. According to the standard method in GB / T 2419-2005 "Method for Determination of Fluidity of Cement Mortar", the early strength agent dosage was fixed at 0.5%, and the amount of Point-KZJ admixture was adjusted to form the mortar fluidity within the range of 180mm±5mm; the mortar compressive strength test was carried out in accordance with GB / T 17671-1999 "Method for Testing Strength of Cement Mortar (ISO)", and the test results are shown in Table 1.

[0053] Table 1 Early strength performance test of cement mortar

[0054]

[0055] Experiments show that to ensure that the mortar molding fluidity is within the range of 180mm±5mm, the amount of admixture required for Examples 1 to 3 is lower than that for Comparative Examples 1 to 4, indicating that the mortar dispersion performance of Examples 1 to 3 is better than that of the comparative examples, among which the amount of admixture used in Comparative Example 3 increases the most and its dispersion performance is the worst. From the results of the mortar 1d early strength, it can be found that Example 1 has the highest 1d strength and the best mortar reinforcement effect, followed by Example 3 and Example 2. The early strength of the mortars of Comparative Examples 1 to 4 is in the following order: Comparative Example 3>Comparative Example 4>Comparative Example 2>Comparative Example 1.

[0056] According to GB 8076-2008 "Concrete Admixtures" standard, the above embodiments and comparative examples were subjected to cement concrete working performance tests, with a fixed water-binder ratio of 0.45 and admixture and early strength agent dosages. The concrete mix ratio is shown in Table 2, and the concrete performance test results are shown in Table 3.

[0057] Table 2 Concrete mix ratio

[0058] cement sand gravel water Admixtures Early strength agent <![CDATA[360kg / m 3 ]]> <![CDATA[810kg / m 3 ]]> <![CDATA[1020kg / m 3 ]]> <![CDATA[162kg / m 3 ]]> 2.1% 1.5%

[0059] Table 3 Concrete working performance test

[0060]

[0061] The experimental results show that the concretes of Examples 1 to 3 have better initial expansion and initial slump. Among them, the early strength performance of Comparative Example 4 is slightly different from that of the examples, while the concrete working performance of Comparative Example 3 is the worst, and the concrete of Comparative Example 1 has the largest reduction in early compressive strength and the worst strengthening performance. It can be seen that the use of nano-silicon calcium component and the specific first modifying component, second modifying component, third modifying component, and fourth modifying component can effectively improve the early strength performance of cement mortar and concrete through the synergistic promotion between each other.

[0062] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations on the present invention. A person skilled in the art may change, modify, replace and modify the above embodiments within the scope of the present invention without departing from the principles and purpose of the present invention.

Claims

1. A concrete early strength agent, characterized in that: The concrete early strength agent contains a nano-calcium silicon component, a first modifying component, a second modifying component, a third modifying component and a fourth modifying component, as well as an optional neutralizing agent and water. The nano-calcium silicon component contains both a nano-silica component and a nano-calcium component. The first modifying component is obtained by hydrolysis and condensation reaction of a silicate compound, an organic siloxane compound, an inorganic silicon compound and / or nano-microcrystalline cellulose in the presence of a cationic compound and a dispersion stabilizer. The second modifying component contains both a polyol and a carboxylate and / or a (sub)nitrate. The third modifying component is a hydrophobic surfactant. The fourth modifying component is a polymer with a long side chain steric hindrance effect.

2. The concrete early strength agent according to claim 1, characterized in that: The weight ratio of the nano-silicon calcium component, the first modified component, the second modified component, the third modified component, the fourth modified component and water is 100:(150-300):(90-160):(10-40):(180-320):(2500-3500); the amount of the neutralizer is based on controlling the pH value of the concrete early strength agent to 6-7.

3. The concrete early strength agent according to claim 2, characterized in that: The content of the nano-silicon calcium component is 13 to 16 parts by weight, the content of the first modified component is 25 to 35 parts by weight, the content of the second modified component is 15 to 20 parts by weight, the content of the third modified component is 2 to 5 parts by weight, the content of the fourth modified component is 30 to 40 parts by weight, and the content of water is 400 to 420 parts by weight.

4. The concrete early strength agent according to claim 1, characterized in that: The mass ratio of the nano-silicon component to the nano-calcium component is (10-15):(18-23); Preferably, the nano-silica component is selected from at least one of sodium metasilicate pentahydrate, sodium metasilicate nonahydrate, tetraethyl orthosilicate, tetrabutyl orthosilicate, potassium silicate, lithium silicate and sodium orthosilicate; Preferably, the nano calcium component is a soluble calcium source; Preferably, the soluble calcium source is selected from at least one of calcium formate, calcium acetate, calcium chloride, calcium gluconate and calcium nitrate tetrahydrate.

5. The concrete early strength agent according to claim 1, characterized in that: The mass ratio of the silicate compound, the organosiloxane compound, the inorganic silicon compound and / or the nano-microcrystalline cellulose, the dispersion stabilizer and the cationic compound used in the preparation process of the first modified component is (10-20):(15-18):(25-30):(40-50):(5-8); Preferably, the silicate compound is selected from at least one of ethyl orthosilicate, propyl orthosilicate, tetraethyl orthosilicate, tetrabutyl orthosilicate, trimethylsilyl acetate, ethyl trimethylsilyl acetate and trimethylsilyl acetate; Preferably, the organosiloxane compound is selected from at least one of vinyl tris(2-methoxyethoxy)silane, γ-aminopropyl triethoxysilane, γ-(2,3-epoxypropyloxy)propyl dimethylethoxysilane, γ-methacryloxypropyl trimethoxysilane and allyl triethoxysilane; Preferably, the inorganic silicon compound is selected from at least one of nano silicon dioxide, sodium silicate, potassium silicate and aluminum silicate; Preferably, the dispersion stabilizer contains both a nonionic surfactant and a dispersion solvent; Preferably, the cationic compound is at least one selected from hexadecyltrimethylammonium chloride, tetradecyldimethylbenzylammonium chloride, methacryloyloxyethyltrimethylammonium chloride, dimethylaminoethyl methacrylate and trimethylammoniumethyl methacrylate; Preferably, the conditions of the hydrolysis condensation reaction include a temperature of 40° C. to 50° C. and a time of 1 h to 5 h.

6. The concrete early strength agent according to claim 1, characterized in that: The mass ratio of the content of the polyol in the second modified component to the total content of the carboxylate and the (nitrite) is (1-5):(15-25); Preferably, the polyol is selected from at least one of ethylene glycol, diethylene glycol, glycerol and diethylene glycol; Preferably, the carboxylate is selected from at least one of calcium formate, potassium formate, sodium formate, calcium acetate, potassium acetate and sodium acetate; Preferably, the (sub)nitrite is selected from at least one of sodium nitrite, potassium nitrite, calcium nitrite, sodium nitrate, potassium nitrate and calcium nitrate.

7. The concrete early strength agent according to claim 1, characterized in that: The third modifying component is selected from at least one of octadecyltrimethylammonium chloride, cocamidopropyl betaine, lauramidopropyl hydroxysulfobetaine, cocamidopropyl hydroxysulfobetaine and sodium α-olefin sulfonate.

8. The concrete early strength agent according to claim 1, characterized in that: The fourth modified component is selected from at least one of acrylic polymers, methacrylic polymers, polyamide, polyimide, polyethylene and polyethylene glycol; preferably, the number average molecular weight of the fourth modified component is 3000-6000 g / mol.

9. The concrete early strength agent according to claim 1, characterized in that: The neutralizing agent is selected from at least one of sodium methoxide, sodium hydroxide, potassium hydroxide, sodium bicarbonate, potassium bicarbonate, sodium acetate, potassium acetate, dimethylethanolamine and triisopropanolamine.

10. The method for preparing the concrete early strength agent according to any one of claims 1 to 9, characterized in that: The method comprises the steps of uniformly mixing a nano-silicon calcium component, a first modified component, a second modified component, a third modified component, a fourth modified component, an optional neutralizer and water to obtain the concrete early strength agent.

11. The method for preparing a concrete early strength agent according to claim 10, characterized in that: The mixing method comprises the following steps: S1. Dispersing the nano-silicon component and the nano-calcium component in the fourth modified component II to obtain a product containing the nano-silicon-calcium component; dissolving the cationic compound and the dispersion stabilizer in the fourth modified component I to obtain a dispersion, and then dropping a mixture of a silicate compound, an organic siloxane compound, an inorganic silicon compound and / or nano-microcrystalline cellulose into the dispersion at 40°C to 50°C, and keeping the mixture warm after the addition is completed to obtain a product containing the first modified component; uniformly mixing the polyol with the carboxylate and / or (sub)nitrate to obtain a second modified component; S3. The product containing nano-silicon calcium component, the third modified component and the fourth modified component are mixed evenly, the resulting composite liquid is mixed evenly with the product containing the first modified component and the second modified component, and then the pH value of the resulting mixed liquid is adjusted to 6 to 7 using a neutralizer to obtain a concrete early strength agent.

12. Use of the concrete early strength agent according to any one of claims 1 to 9 in low-temperature concrete.